2013
DOI: 10.1093/heapol/czt089
|View full text |Cite
|
Sign up to set email alerts
|

Increasing institutional deliveries among antenatal clients: effect of birth preparedness counselling

Abstract: The World Health Organization recommends birth and emergency preparedness (BEP) as essential components of the Focused Antenatal Care model. The purpose of providing BEP messages to women during their antenatal visits is to increase the use of skilled attendance at childbirth. However, the effectiveness of this component has not yet been clearly established in routine contexts. This retrospective cohort study examined the association between exposing women to BEP messages during antenatal visits and the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…It indicates that bicycles are more common as the means of transport compared to motorbikes among women seeking healthcare during pregnancy and childbirth in Burkina Faso. On this topic, a study conducted in north-western Burkina Faso showed a positive correlation between the availability of a motorbike in the woman’s household and their use of a health facility for delivery [23]. Further studies are needed to explore how a mode of transport correlates with the utilization of maternal healthcare in Burkina Faso.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that bicycles are more common as the means of transport compared to motorbikes among women seeking healthcare during pregnancy and childbirth in Burkina Faso. On this topic, a study conducted in north-western Burkina Faso showed a positive correlation between the availability of a motorbike in the woman’s household and their use of a health facility for delivery [23]. Further studies are needed to explore how a mode of transport correlates with the utilization of maternal healthcare in Burkina Faso.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the distance to health facilities, we analyzed if the availability of means of transport at the community-level was associated with the use of maternal healthcare. DHS did not include information on public transport, but asked questions about whether or not the household owned a bicycle and motorbike, which are the popular means of transport in Burkina Faso even among women in seeking healthcare during pregnancy and childbirth [23]. We thus calculated the ownership rates of bicycles and motorbikes per cluster and used them as proxy variables for the community-level availability of means of transport.…”
Section: Methodsmentioning
confidence: 99%
“…Although Birth Preparedness or Complication readiness (BPCR) is a broad and integrative strategy, lack of evidence exists in relation to its comprehensive and holistic application. However, components of the BPCR matrix have been employed and assessed in many settings [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Villar [9] in a multicenter study that involved 12,568 women in the new model arm and 11,958 in the standard care arm showed that there was really no statistically significant difference in adverse maternal and foetal outcomes in women who received traditional care and focused antenatal care. However, the focused antenatal care model has been shown to increase utilization of skilled attendance at birth and it is also cost effective [15][16][17].…”
Section: Introductionmentioning
confidence: 99%